2023
DOI: 10.1002/adfm.202212037
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Orthogonal Upconversion through Selective Excitation in a Single Nanoparticle

Abstract: Orthogonal upconversion with color‐switchable emissions under different excitation conditions provides new chances to diverse frontier applications of luminescent materials. However, the previous orthogonal upconversion systems compulsorily require the precise control of spatial distributions of dopants and host compositions to avoid spectral cross‐talk, greatly limiting their synthesis and application. Herein, a conceptual design is presented to realize the orthogonal upconversion by selectively activating se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Multicolor information encryption has been garnering increasing attention owing to its powerful confidentiality features in the field of anticounterfeiting. Because the aUCNPs had a primary green emission at 544 nm and a relatively weak red emission at 664 nm, a simple, fast, and multicolor information encryption strategy was developed using IFE. First, the hydrophilic aUCNPs were obtained by modifying Tween 20 through the hydrophobic effect (Figures S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Multicolor information encryption has been garnering increasing attention owing to its powerful confidentiality features in the field of anticounterfeiting. Because the aUCNPs had a primary green emission at 544 nm and a relatively weak red emission at 664 nm, a simple, fast, and multicolor information encryption strategy was developed using IFE. First, the hydrophilic aUCNPs were obtained by modifying Tween 20 through the hydrophobic effect (Figures S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide-doped materials exhibit excellent luminescent properties through various energy conversion mechanisms, giving rise to luminescence effects such as upconversion, downshifting, and afterglow. [23][24][25][26][27][28] While current research is mainly focused on upconversion and downshift luminescence based on lanthanide ions, [29][30][31][32][33][34] recent studies have also shown great interest in developing afterglow luminescence for information encryption and anti-counterfeiting, enhancing information security luminescence for information encryption and anticounterfeiting to further enhance the information security. [35][36][37][38][39] Distinct from photoluminescence, afterglow luminescence operates without real-time excitation, thus mitigating background noise interference.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lanthanide-doped nanoparticles have attracted a lot of attention in many fields due to their high photostability, low cytotoxicity, long luminescence lifetime, and weak background noise. [1][2][3][4][5][6] Benefiting from the special electronic structure of lanthanide, they are able to achieve both upconversion and downshifting emission under the same wavelength excitation, thus covering a broad spectral emission region from ultraviolet to near-infrared (NIR). These rich emission bands are regarded as DOI: 10.1002/adom.202302880 a prerequisite for modulating the luminescent properties of the material, [7][8][9] which has always been a primary focus of fluorescence technology.…”
Section: Introductionmentioning
confidence: 99%